2005
DOI: 10.1007/s00109-005-0717-6
|View full text |Cite
|
Sign up to set email alerts
|

Human low-density lipoprotein receptor gene and its regulation

Abstract: The low-density lipoprotein (LDL) receptor is a transmembrane glycoprotein that mediates the binding and endocytosis of lipoproteins containing apolipoprotein B and E, especially the cholesterol-rich LDL. Mutations in the LDL receptor gene can produce dysfunctional LDL receptors and cause familial hypercholesterolemia. The expression of the LDL receptor gene is under an intriguing regulation by sterol and nonsterol mediators either at the transcriptional level or at the posttranscriptional level, both of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 81 publications
3
35
0
1
Order By: Relevance
“…However, the cholesterollowering efficacy of BBR seems to be mainly attributable to LDL receptor up-regulation. 3,4) Our previous results showed that BBR increased LDL receptor mRNA stability and expression level in an extracellular signal-regulated kinase (ERK)-dependent manner; as BBR could activate ERK directly in liver cells and U0126, a specific inhibitor of mitogen-activated protein kinase kinase (MAPKK or MEK) could abolish the effects of BBR on LDL receptor.4) These results suggest that BBR up-regulates LDL receptor through the ERK MAPK signal-transduction pathway which may include the sequential activation of three kinases: Raf-1, MEK, and ERK.12) The ERK MAPK cascade could be activated by various extracellular stimuli and could help to transduce signals from cell surface to nucleus. Numerous studies demonstrate that the ERK MAPK cascade has close relationship to cell proliferation, differentiation, migration and death.…”
mentioning
confidence: 99%
“…However, the cholesterollowering efficacy of BBR seems to be mainly attributable to LDL receptor up-regulation. 3,4) Our previous results showed that BBR increased LDL receptor mRNA stability and expression level in an extracellular signal-regulated kinase (ERK)-dependent manner; as BBR could activate ERK directly in liver cells and U0126, a specific inhibitor of mitogen-activated protein kinase kinase (MAPKK or MEK) could abolish the effects of BBR on LDL receptor.4) These results suggest that BBR up-regulates LDL receptor through the ERK MAPK signal-transduction pathway which may include the sequential activation of three kinases: Raf-1, MEK, and ERK.12) The ERK MAPK cascade could be activated by various extracellular stimuli and could help to transduce signals from cell surface to nucleus. Numerous studies demonstrate that the ERK MAPK cascade has close relationship to cell proliferation, differentiation, migration and death.…”
mentioning
confidence: 99%
“…The LDL-receptor uptake and clear LDL-C from circulation. This receptor is regulated at the transcriptional or posttranscriptional level (Kong et al, 2006). Simvastatin induced the upregulation of the LDL receptor gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is supported by the moderate upregulation of the low density lipoprotein receptor (LDLR) at 3 and 5 h pt (3.4-and 3.3-fold, respectively) via the ERK pathway (74). LDLR is synthesized in the rough ER (73).…”
Section: Is a Function Of Pnpla8 [Intracellular Membrane-associated Cmentioning
confidence: 95%